2020
DOI: 10.3856/vol48-issue3-fulltext-2419
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput sequencing of the 16S rRNA gene to analyze the gut microbiome in juvenile and adult tropical gar (Atractosteus tropicus)

Abstract: Tropical gar (Atractosteus tropicus) is freshwater and estuarine fish, inhabiting the Earth since the Mesozoic era and undergoing limited physiological variation ever since. Besides its recognized cultural andscientific relevance, the species has seen remarkable growth in its economic impact due to pisciculture. In this study, we present the first report of the whole taxonomic composition of microbial communities in gut contents in juveniles and adults of A. tropicus, by sex and origin (wild and cultiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 107 publications
2
3
0
Order By: Relevance
“…The composition of Fusobacteria and Proteobacteria in E. stellifer is similar to that found in other marine fish, such as Silurus and Carassium 24 , and to results reported for freshwater garpike 32 . A few studies have shown Fusobacteria to be the dominant members of the gut microbiota of freshwater fish 33 , 34 .…”
Section: Discussionsupporting
confidence: 86%
“…The composition of Fusobacteria and Proteobacteria in E. stellifer is similar to that found in other marine fish, such as Silurus and Carassium 24 , and to results reported for freshwater garpike 32 . A few studies have shown Fusobacteria to be the dominant members of the gut microbiota of freshwater fish 33 , 34 .…”
Section: Discussionsupporting
confidence: 86%
“…Gut microbial alpha diversity did not differ between the sexes in G. japonicus, similar to the result reported for a wide range of vertebrates including fish [61], amphibians [62], birds [57], and mammals [63]. However, sexual differences in gut microbial diversity do exist in many animals, also including fish [64], birds [65], and mammals [66]. Taken together, available data show that dietary and/or sexual correlates of host gut microbial alpha diversity are species-or taxonspecific.…”
Section: Discussionsupporting
confidence: 85%
“…Gut microbial alpha diversity did not differ between the sexes in G. japonicus , similar to the results reported for a wide range of vertebrates, including fish [ 62 ], amphibians [ 63 ], birds [ 58 ], and mammals [ 64 ]. However, sexual differences in gut microbial diversity do exist in many animals, including fish [ 65 ], birds [ 66 ], and mammals [ 67 ]. Taken together, the available data show that dietary and/or sexual correlates of host gut microbial alpha diversity are species- or taxon-specific.…”
Section: Discussionmentioning
confidence: 99%